How well are clinical gross tumor volume DVHs approximated by an analytical function? - Stavrev, Pavel (Radiology and oncology (Ljubljana), 2009)
The dose heterogeneity in the tumor is often described as being normally distributed. Besides the normal distribution we propose the Fermi function describing Fermi statistics as a possible dose heterogeneity descriptor. In order to demonstrate the adequacy of the proposed functions as dose distribution descriptors 30 clinical gross tumor volume (GTV) dose-volume histograms (DVHs) are gathered and fit with the examined functions.
Keywords: Dose-Response Relationship, Drug; Doza-odgovor, odnos, zdravilo; doziranje; Drug Therapy; Modeli statistični; Models, Statistical; Neoplasms; Novotvorbe; onkologija; radioterapija; statistični modeli; tumor; tumorji